Tư tưởng Hồ Chí Minh về phát triển văn hóa, xây dựng con người - Đặng, Xuân Kỳ (2011)
Tác giả: Đặng Xuân Kỳ, GS; Vũ Khiêu; Hoàng Chí Bảo; Đỗ Huy; Thành Duy; Song Thành; Đỗ Quang Hưng; Lê Văn Tích; Phạm Hồng Chương; Phan Minh Hiền -- Từ khóa: Tư tưởng Hồ Chí Minh; Văn hóa; Con người; Hồ Chí Minh; Lịch sử tư tưởng